Controle de qualidade de próteses removíveis totais mucossuportadas: sistematização de um instrumento de avaliação protética - Santos, Vera Lúcia Jerônimo dos (2009)
Most of the dentistry professionals indicate the replacement of Complete Denture (TRPs) after five years of useful life, for they believe that that it is the time, on average, of durability of a removable prosthesis. The main complaint of the patient's expressed desire in modifying or keeping the buccal reality, the morpho-functional conditions of TRP, are factors that influence on decision making regarding the type of planning of mucous supported and/or implanted TRP's on keeping, repairing or replacing them. The analysis shows that a meticulous anamnesis and clinical exam are essential, in order to know and list data collected to be set as favorable or unfavorable. This way, decision making on (non) replacing TRPs is a difficult task and not yet defined in the specialized literature. For this reason, we intended, in this study, to verify the pertinence of subjects that includes physical and functional data of the prosthesis, the opinion and the patient's physiologic condition, with the purpose of elaborating a work instrument that could, in future studies, support the difficult decision taking in maintaining, repairing or substituting PRT. This way, it was elaborated, in a first moment, a quality evaluation instrument of PRT with questions about anamnesis, questionnaires on chewing ability, visual analogical scale, satisfaction with the prosthesis; and still, important items on the base and the TRP teeth. Later, with the internal teachers' aid of the University of Dentistry of the Federal University at Uberlândia and external teachers, respecting the inclusion and exclusion criteria, a note was checked to each subject in agreement with its pertinence and inclusion. The results were analyzed by a descriptive statistics, where the participation of 77,8% internal and 11,8% external educational ones was observed. The subjects suffered some alterations in agreement with its punctuation, in order to adapt the original instrument giving it a new critical format.